Urbanization, Colonization and Underdevelopment in the Bas-Saint-Laurent : Fraserville and the Témiscouata in the Late Nineteenth Century - Willis, John (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1984)
This paper is based on the premise that regional differentiation is intrinsic to the formation of contemporary capitalist society. Informed by current dependence theory, we discuss the applicability of the agri-forestry concept to the experience of one Bas-Saint-Laurent sub-region (the Témiscouata) during the late XIXth Century period. The agri-forestry System, it is argued, impoverished agriculture and fragmented the county economy between a rural forestry sector and an urban railroad one. It was, in short, the prime agency of underdevelopment in the Bas-Saint-Laurent.